Prototype Pengaman Rumah Dari Bahaya Pencurian Berbasis Mikrokontroller Melalui Komunikasi Bluetooth - Safitri, Meutia; Raka Agung, I Gusti Agung Pt.; Diafari Djuni, I Gst A. Komang (Jurnal SPEKTRUM; Vol 6 No 2 (2019): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2019.v06.i02.p08, 2019)
The negligence of residents and the lack of a house security system are the causes of the rampant cases of theft. Technological developments are increasingly rapid, making technology can be applied as a security system at home. This can be a solution to these problems. In this study a home security system was developed in the form of a prototype. This study uses a microcontroller that can be controlled using mobile devices via bluetooth communication. The prototype consists of a keypad to enter a password as a substitute for a home key, a PIR sensor as a detection of human body heat movements, and a buzzer as an alarm. The results of this study are that the prototype has been realized where the servo motor has been able to open and lock by entering the correct password. Setting ON / OFF lighting, display information on the LCD, and ON / OFF PIR sensor from an Android mobile phone via Bluetooth communication are in accordance with the plan.